Konstruksi Nilai-Nilai Pancasila dalam Tradisi Pasola Sebagai Representasi Kearifan Lokal Masyarakat Sumba (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to construct the values of the Pancasila in the Pasola tradition as a representation of the local wisdom of the Sumba community. The study used a qualitative approach with a critical ethnographic method, conducted in the Kodi region of Sumba Barat Daya. Data dikumpulkan melalui observasi partisipatif, wawancara mendalam, dan studi dokumentasi, dan dianalisis dengan model Miles, Huberman, dan Saldaña, dengan menggunakan analisis tematik dan konstruksi sosial. The results of the study show that Pasola contains religious values, social solidarity, leadership, conflict resolution, and a balance between humans and nature, which are rooted in the Marapu belief system. Pasola also represents the five principles of the Indonesian national philosophy, Pancasila: Ketuhanan (religiousness), Kemanusiaan (humanity), Persatuan (unity), Kerakyatan (democracy), and Keadilan Sosial (social justice). The process of constructing these values takes place through the stages of externalisation, objectification, and internalisation in the lives of the community. This study confirms that the values of the Pancasila are deeply rooted in local traditions and shows the potential of Pasola as a source of contextual learning in the teaching of the Pancasila based on ethnopedagogy to strengthen the character and cultural identity of students